Profissionais do sexo feminino em três áreas do ceará : fatores que ampliam a vulnerabilidade para DST/AIDS - Macena, Raimunda Hermelinda Maia (2009)
Prostitution can be found in any country, regardless of their level of development. This occupation exposes the individual to a wide range of health risks. This study documents, sectional investigated risk factors for HIV and other STDs among female sex workers in three geographical areas of Ceara. Factors related to socio-demographic profile, knowledge and practices concerning STD / AIDS, prevalence of infection by HIV and Treponema palidum were related to engaging in unprotected sex. The sample consisted of 819 women who reported sexual practice paid within 180 days preceding the survey recruited through snowball in the cities of Fortaleza, Sobral, Juazeiro and Crato, between February and November 2003. The analysis was performed using STATA, version 10.0. The prevalence of HIV and syphillis was 2.1% and 19.5%, respectively. Most are young women (<28anos; 64.6%), brown (61.1%) with incomplete primary education (56.6%), with stable relationships past (44.1%), working in bars (54 2%) and brothels (17.5%) with high frequency of alcohol weekly (44.2%). Sexual behavior reveals involvement in unprotected sex (35.1%). Prostitution was characterized by an average of seven different partners in the last seven (7) days of realiação the study, collection of low values.